A Rare and Potentially Catastrophic Infection: Primary Intestinal Aspergillosis—Case Report in an HIV Patient - Cátia Dias; Filipa Duarte-Ribeiro; Sara Pipa; Margarida Mota (Case Reports in Infectious Diseases)
Aspergillus species are ubiquitous in nature; however, infection is uncommon, except in immunocompromised or immunosuppressed hosts. We present the case of a 71-year-old woman with a history of human immunodeficiency virus infection who presented with fever, weight loss, and diarrhea, posteriorly diagnosed with intestinal aspergillosis after examination of a segmental enterectomy piece. The diagnosis was made postmortem once the patient died after fast and progressive deterioration in the postoperative period.